Trends and Challenges of Chronic Occupational Morbidity in Ukraine: A Sectoral Analysis and Preventive Strategies - Mezentseva, Iryna; Kuzmenko, Olena; Vambol, Sergij; Mezentsev, Serhii; Vambol, Vladyslava (Diversity: Disease Preventive of Research Integrity, 2025)
Occupational morbidity remains a critical public health issue worldwide, including in Ukraine, where the prevalence of chronic occupational diseases has shown an increasing trend. High-risk industries, particularly the mining sector, exhibit alarming rates of chronic occupational diseases, mainly affecting the respiratory system, musculoskeletal structure, and auditory functions. This study aims to analyze trends and causes of chronic occupational morbidity in Ukraine from 2016 to 2022, utilizing statistical data and quantitative analysis. The findings indicate that the primary contributing factors to chronic occupational diseases include outdated technological processes, inadequate working tools, and the failure to use personal protective equipment. The study recommends strengthening medical surveillance by reducing the interval between health examinations, enhancing labor protection training, and implementing stricter industrial hygiene regulations. These findings underscore the urgent need for policy reforms and workplace interventions to mitigate occupational morbidity and protect workers’ health. From an ethical and religious perspective, ensuring a safe and healthy work environment aligns with Islamic teachings that emphasize justice, fairness, and the well-being of workers.